If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + 12 = 6 Reorder the terms: 12 + -1x = 6 Solving 12 + -1x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -1x = 6 + -12 Combine like terms: 12 + -12 = 0 0 + -1x = 6 + -12 -1x = 6 + -12 Combine like terms: 6 + -12 = -6 -1x = -6 Divide each side by '-1'. x = 6 Simplifying x = 6
| -z+2=13 | | 67=21x | | 4n-6-5n=8-n+7 | | 1/2×-2=2-5/3× | | 21xy/20x | | .16x+.6(x-4)=.01(3x-3) | | t-5+6t=3(3t-3) | | -6(4x-4)+8=-24x+32 | | 5p+3=3(3p-5) | | 2n+59=-4-5n | | -16+5n=-7-6+8n | | -3y/-3=25/-3 | | 7=1/2(-m-5) | | (1-4p)/50.2 | | 24=15-(4z-3) | | 21=-6m+39 | | 5k-6=-31 | | 4-3[2-(4y-5)]= | | -4(2x-3)=-8n-20 | | 7x^2-19x-8= | | 2x+33=162 | | 21/6/4 | | 81x+9y=72 | | 5(r+9)-2(-1-r)=1 | | 11.4=-14.2+4u | | 6x^2+2x=1 | | -4x+9x=3 | | -10=y/3-4 | | 33=172-u | | 56*x/7 | | -y+25=160 | | 141-x=201 |